2014
DOI: 10.1097/dcr.0000000000000090
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Extended Postoperative Venous Thromboembolism Prophylaxis in IBD

Abstract: Patients with IBD had a significantly increased risk for postoperative venous thromboembolism in comparison with patients who had colorectal cancer. Therefore, postdischarge venous thromboembolism prophylaxis recommendations for IBD patients should mirror that for patients who have colorectal cancer. This would suggest a change in clinical practice to extend out-of-hospital prophylaxis for 4 weeks in postoperative IBD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 9 publications
0
52
0
Order By: Relevance
“…right hemicolectomy, total proctocolectomy (TPC), sigmoidectomy]. Two studies compared the types of operation being performed for IBD and CRC patients . There was no significant difference between laparoscopic and open approaches or for pelvic and abdominal operations between the two groups.…”
Section: Resultsmentioning
confidence: 99%
“…right hemicolectomy, total proctocolectomy (TPC), sigmoidectomy]. Two studies compared the types of operation being performed for IBD and CRC patients . There was no significant difference between laparoscopic and open approaches or for pelvic and abdominal operations between the two groups.…”
Section: Resultsmentioning
confidence: 99%
“…Several authors have noted the high rates of postoperative venous thromboembolism in IBD patients and have suggested the extended use of venous thromboembolism prophylaxis [64][65][66]69] along the same lines as in current standard practice for patients undergoing colorectal cancer resection.…”
Section: Risk Of Venous Thromboembolism In Patients Requiring Surgerymentioning
confidence: 99%
“…Hospitalization was associated with higher costs ($47515 vs $21499, P < 0.0001) and higher mortality (adjusted OR = 2.5, 95%CI: 1.83-3.43) in IBD patients compared with controls[85]. IBD patients undergoing surgery have an increased risk for postoperative VTE (OR = 1.26, 95%CI: 1.021-1.56, P = 0.03) compared with patients undergoing surgery for colorectal cancer[86]. Therefore, it has been suggested that VTE prophylaxis in postoperative IBD patients be extended out-of-hospital for 4 wk after discharge[87,88].…”
Section: Prevention Of Venous Thromboembolismmentioning
confidence: 99%